Concomitant presentation and surgical management of an abdominal aortic aneurysm and translocation XP11.2 associated renal cell carcinoma in a female infant - Ramón Garcia-Alva; Javier E. Anaya-Ayala; Gabriel Lopez-Pena; Lizeth Luna; Cesar Cuen-Ojeda; Rene Lizola; Eduardo Lopez-Corella; Carlos A. Hinojosa (Elsevier, 2018)
Abdominal Aortic Aneurysms are rare in the infant population, when these occur are secondary to connective tissue diseases, vasculitis, and infectious etiology or in relation with tuberous sclerosis. We herein present an 11 month-girl who was diagnosed with a translocation Xp11.2 associated left renal cell carcinoma (RCC). In addition to this finding, a Computed Tomography Angiography (CTA) revealed a 2.8 centimeters (cm) dilatation of the infrarenal aorta consistent with a fusiform aneurysm. She underwent concomitant left nephrectomy and aneurysm repair with a 14 millimeters (mm) expanded polytetrafluoroethylene (ePTFE) graft. Following the procedure the patient recovered without complications and she was discharged five days later. To our knowledge this is the first concomitant presentation of an abdominal aortic aneurysm and a translocation Xp11.2 RCC in an infant patient treated successfully by tumor resection and aortic reconstruction. At one year of follow up she is developing according to her age without complications.